EFFECTIVENESS OF RADEC-BASED ON IMPROVING LEARNING PLANNING SKILLS AT ELEMENTARY SCHOOL - Anugrah Ramadhan Firdaus; Wahyu Sopandi; Jajang Bayu Kelana; Linda Hania Fasha; Ida Fiteriani; Yusup Maulana (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2023)
Teachers are professional educators with the main task of educating, teaching, guiding, directing, training, assessing, and evaluating students in every teaching and learning process in schools. In the learning process, various skills are needed for the continuity of the learning process, one of which is the skill of making lesson plans. The skill of a teacher in making lesson plans determines the learning outcomes that will be accepted by students. This study aims to analyze the effect of RADEC-based workshop activities in improving the skills of elementary school teachers to make good lesson plans. This study uses the One Group pretest posttest method with a sample of elementary school teachers in Purwakarta Regency. The instrument used is the result of adaptation of the assessment of the learning implementation plan in the PPG program. There are seven indicators used in the instrument used. The results showed that the RADEC model had an impact on teachers in developing learning planning skills. The average n-gain score obtained from this study was 58 which was categorized as quite effective.